Low‐Cost, Large‐Area, Multifunctional Stretchable E‐Tattoos Inspired by Dough Figurines for Wearable Human‐Machine Interfaces. Issue 6 (2nd December 2021) - Niu, Haoran; Li, Min; Yang, Lina; Xu, Baochun; Li, Mingyue; Wang, Hongfei; Guo, Qiuquan; Meng, Zhaosheng; Liu, Yijian; Chen, Da
Abstract: Noninvasive electronic tattoo (e‐tattoo) attached to human skin surface for accurately obtaining various physiological information, has been widely used in wearable human‐machine interfaces (HMIs) for medical care, sports training, and artificial intelligence. The existing preparation technologies of e‐tattoos are difficult to satisfy the requirement of commercial mass production due to their high cost and low time efficiency. Here, inspired by the Chinese folk craftsmanship of dough figurines, a set of one‐step forming embossing process and a thermal‐mismatch‐induced transfer method are proposed for high‐efficient manufacture of low‐cost, large‐area, and multifunctional stretchable e‐tattoos. Benefited from the excellent flexibility and stretchability, the fabricated e‐tattoos can conformably follow the deformation of skin and collect high‐quality bioelectrical signals. Moreover, it can maintain good mechanical and electrical properties even when stretched to 40%. As a proof‐of‐concept, the 5‐µm‐thick e‐tattoo electrodes with hollow‐out and serpentine design are fabricated and demonstrated for the wearable HMI applications of electrocardiogram, electromyogram, brain training, epidermal heating, and flexible interconnection. Therefore, this cost‐effective and high‐fidelity e‐tattoo provides a potential path for the wearable HMI of widespread, non‐irritating, and multifunctional. Abstract : Inspired by the Chinese folk craftsmanship of dough figurines, this paper proposes a set of one‐step forming embossing process and a thermal‐mismatch‐induced transfer method for high‐efficient manufacture of low‐cost, large‐area, and multifunctional stretchable e‐tattoos. In addition to vital sign monitoring, mass‐produced e‐tattoos open up promising functions in wearable human‐machine interfaces, such as brain training, epidermal heating, and flexible interconnection.